Structural insights into functional overlapping and differentiation among myosin V motors - Nascimento, A; Trindade, D; Tonoli, C; De Giuseppe, P; Assis, L; Honorato, R; Deoliveira, P; Mahajan, P; Burgess-Brown, N; von Delft, F; Larson, R; Murakami, M (2013)
Myosin V (MyoV) motors have been implicated in the intracellular transport of diverse cargoes including vesicles, organelles, RNA-protein complexes, and regulatory proteins. Here, we have solved the cargo-binding domain (CBD) structures of the three human MyoV paralogs (Va, Vb, and Vc), revealing subtle structural changes that drive functional differentiation and a novel redox mechanism controlling the CBD dimerization process, which is unique for the MyoVc subclass. Moreover, the cargo- and motor-binding sites were structurally assigned, indicating the conservation of residues involved in the recognition of adaptors for peroxisome transport and providing high resolution insights into motor domain inhibition by CBD. These results contributetounderstanding the structural requirements for cargo transport, autoinhibition, and regulatory mechanisms in myosin V motors. © 2013 by The American Society for Biochemistry and Molecular Biology, Inc Published in the U.SA. © 2013 by The American Society for Biochemistry and Molecular Biology, Inc.